A 2D dual-mode composite ultrasonic transducer excited by a single piezoceramic stack. (21st December 2018) - Xu, Long; Qiu, Xiaojun; Zhou, Jincheng; Li, Fengming; Zhang, Haidao; Wang, Yuebing
Abstract: A 2D composite ultrasonic transducer with two resonance modes is proposed by using a central coupling metal block, a piezoceramic stack and four outer metal cylinders. With the introduction of the dual-mode equivalent mechanical coupling coefficient and the 2D longitudinal force transform coefficient, a novel equivalent circuit model is developed for the design and analysis of the 2D coupled vibration of the transducer. After verifying the proposed equivalent circuit model with the FE method and the corresponding experiments, the vibration characteristics of the proposed transducer are investigated by using the equivalent circuit mode, the FE methods, and the experiments. The results demonstrate that the proposed transducer has the advantage of generating 2D ultrasonic radiation with two different fundamental resonance modes, which is useful in some new ultrasonic applications such as ultrasonic emulsification, ultrasonic defoaming and ultrasonic sonochemistry where multi-frequency and multidimensional sound radiation is needed.